A wrinkle in time - L'Engle, Madeleine 1918-2007 (Square Fish/Farrar Straus Giroux, 2012)
Meg Murry and her friends become involved with unearthly strangers and a search for Meg's father, who has disappeared while engaged in secret work for the government